The benefits of English-speaking group for speaking fluency: Acehnese EFL students perceptions - Fhonna, Rahmi (Accentia: Journal of English Language and Education, 2023)
As speaking is essential to be mastered, various strategies are applied, one of them is through English-speaking group. The objective of this study is to explore more about the students point of view regarding the beneficial impact of English-speaking group for speaking fluency. Interview was selected as the data collection procedure in this study, in which five female students from Intermediate Language Skill class were participated in this study as the respondents. They were the second semester students at English Language Education Department of Universitas Islam Negeri (UIN) Ar-Raniry Banda Aceh. The results of this study revealed that the participants showed positive responses toward forming English-speaking group as it gave great effects on their speaking fluency. They stated that this speaking group provided supportive environment for speaking activity, increased their confidence, improved self-evaluation, and strengthened the relationship among the members of the group.